Exploring Mental Disorder Students’ Reading Strategies in an Emergency Remote Teaching: A Case from Indonesia - Fauziatur Rakhmah; Luluk Sri Agus Prasetyoningsih (International Journal of Language Teaching and Education, 2022)
Abstract: All students must have the ability to read and the reading ability of each student is of course different. For example, mentally retarded students in grade 5 SDLB C Kemala Bhayangkari 2 Gresik who have deficiencies in reading, because their intellectual ability is below 70. This study aims to describe strategies for learning to read at the beginning of mentally retarded children SDLB C KB 2 Gresik in limited PTM. This research uses a qualitative approach with a case study type. The primary data sources for this study were class teachers and mentally retarded students in grade 5 with poor reading skills. Retrieval of research data is done through observation, interviews, and documentation. The results of this study indicate (1) mentally retarded students in grade 5 SDLB C KB 2 Gresik at limited PTM have different characteristics, both in terms of their physical, behavioral, abilities and IQ, (2) planning carried out by the teacher in learning to read beginning namely making prota, promissory notes, syllabus, and lesson plans in one semester, (3) The implementation of the strategies used by the teacher in learning early reading varies according to the level or type of intellectual disability, characteristics, and abilities of each student, and ( 4) The evaluation carried out by the teacher in learning to read at the beginning is to report to parents, carry out self-assessment and evaluation. Keywords: learning strategies, beginning reading, mentally retarded children, limited PTM